Monitored needle acceleration in endoscopic ultrasound-guided fine-needle aspiration of solid pancreatic masses improves sample quality and diagnostic accuracy: a randomized trial - Ciocîrlan, Mihai; Gheorghiu, Anca; Bilous, Dana; Cruceru, Miruna; Mănăilă, Georgiana; Tianu, Elena; Vlăduţ, Cătălina (Endoscopy, 2021)
Background Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is recommended for the diagnosis of solid pancreatic masses. We aimed to evaluate whether a high needle movement acceleration value during puncture increases diagnostic accuracy.Methods EUS-FNA needle acceleration was measured using a PocketLab accelerometer connected by Bluetooth to a smartphone. Two passes (fast and slow, with higher and lower than 1g [9.8 m/s2] needle acceleration values, respectively) were performed in a random order. The sample cellularity and quality were measured using semiquantitative scales. Results 51 patients were included (32 women; mean age 63). The mean (standard deviation [SD]) acceleration values were 1.59g (0.66g) for the fast pass and 0.32g (0.19g) for the slow pass (P < 0.001). The fast pass yielded significantly higher levels of EUS-FNA accuracy (84.3 % vs. 68.6 %; P = 0.02) and adequate quality scores (94.1 % vs. 76.5 %; P = 0.007). High cellularity scores were seen with similar frequencies (15.7 % vs. 11.8 %; P = 0.32).Conclusions A higher than 1g EUS-FNA needle acceleration may increase the diagnostic accuracy and specimen quality from solid pancreatic lesions.